Pair invariant mass to isolate background in the search for the chiral magnetic effect in Au + Au collisions at √sNN = 200 GeV - Abdallah, Mohamed Samy; Deppner, Ingo Martin; Herrmann, Norbert; Söhngen, Yannick; Weidenkaff, Philipp (Physical review, 2022)
Quark interactions with topological gluon configurations can induce local chirality imbalance and parity violation in quantum chromodynamics, which can lead to the chiral magnetic effect (CME)—an electric charge separation along the strong magnetic field in relativistic heavy-ion collisions. The CME-sensitive azimuthal correlator observable (Δγ) is contaminated by background arising, in part, from resonance decays coupled with elliptic anisotropy (v2). We report here differential measurements of the correlator as a function of the pair invariant mass (minv) in 20-50% centrality Au+Au collisions at √sNN=200 GeV by the STAR experiment at the BNL Relativistic Heavy Ion Collider. Strong resonance background contributions to Δγ are observed. At large minv where this background is significantly reduced, the Δγ value is found to be significantly smaller. An event-shape-engineering technique is deployed to determine the v2 background shape as a function of minv. We extract a v2-independent and minv-averaged signal Δγsig=(0.03±0.06±0.08)×10−4, or (2±4±5)% of the inclusive Δγ(minv>0.4 GeV/c2)=(1.58±0.02±0.02)×10−4, within pion pT=0.2-0.8 GeV/c and averaged over pseudorapidity ranges of −1<η<−0.05 and 0.05<η<1. This represents an upper limit of 0.23×10−4, or 15% of the inclusive result, at 95% confidence level for the minv-integrated CME contribution.
Im Titel stehen die Buchstabes s und "NN" unter dem Wurzelsymbol
Gesehen am 25.01.2023
Star Collaboration: M.S. Abdallah, I.M. Deppner, N. Herrmann, Y. Söhngen, P.C. Weidenkaff [und viele weitere]